MENINGKATKAN PROFESIONALISME GURU DI KABUPATEN PASURUAN MELALUI PENDAMPINGAN MENULIS ARTIKEL DAN PUBLIKASI ILMIAH - Lestari - Setyowati (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
Writing scientific articles requires a skill, especially for teachers who want to improve their careers. However, not all teachers have the skills to write good scientific articles. This community service was carried out in two high schools, and three elementary schools in Pasuruan Regency which was held in the year 2020. The community service involved five lecturers across study programs, namely lecturers from English language education, Indonesian language and literature education, and mathematics education. This service aims to describe 1) the problems encountered by the teacher when writing scientific articles, 2) describe the stages of problem solving, and 3) describe the results that have been achieved during mentoring in writing scientific articles for publication. The problem of identifications show that teachers lack of knowledge and skills regarding how to write abstracts, good background for scientific articles, presentation of discussions, and writing a bibliography. The stages of problem solving are divided into three stages, namely 1) the planning stage, 2) the implementation stage, and 3) the publication stage. The results of the service show that there are three teachers who can meet the minimum standards of scientific articles to be published in scientific journals. The three articles were published in scientific journals selected by their respective authors and are currently published in a national non-accredited journal.